Uses and Gratifications of Arab and Muslim - Oriented Facebook Pages in the U.S.: A Survey of Current users (Global Journal of Human-Social Science, 2014)
Several posts were made on the public walls of over 50 Facebook website that are targeted ad Arabs and Muslims in the West. Participants were asked to fill out an online survey questioning the amount of time they spent using Facebook on a daily basis, the gratifications they obtained from Facebook use, and how they feel about themselves and their culture. In this initial survey, a total of 43 usable responses were obtained - predominantly Saudis living in the USA